Virtual reality-based robotic training for lower limb rehabilitation in stroke patients with Hemiplegia: A pilot study - Lijing Chen; Huanzhi Zhu; Jing Wang; Rongrong Lu; Jing Tian; Bei Wu; Jing Chu; Juan Li (Aging and Health Research)
Background: More than half of stroke survivors suffer from movement disorders after receiving routine rehabilitation treatment. Evidence suggests that virtual reality (VR)-based robotic training for lower limb rehabilitation is a promising approach for improving motor function recovery. Methods: A pilot open-label randomized controlled trial was conducted to explore the feasibility and preliminary effects of VR-based robotic training for lower limb rehabilitation in stroke patients with hemiplegia. We enrolled 42 stroke patients with hemiplegia, 21 received VR-based robotic training for lower limb rehabilitation and conventional rehabilitation treatment as the intervention, and 21 only received conventional rehabilitation treatment as the control. Results: Forty participants completed the trial. We found a statistically significant difference in lower limb motor function scores from baseline to week 4 between the intervention and control group (mean difference (MD): 6.5 vs 3.3, p<0.001). At week 4, participants in the intervention group demonstrated significant enhancements in balancing function, walking ability, activities of daily living, and quality of life (p<0.05). However, the intervention group did not show a significant improvement in global cognitive function compared to the control group (MD: 3.8 vs 3.7, p = 0.873). No adverse events were observed during the trial. Conclusion: The VR-based robotic training for lower limb rehabilitation showed promise in improving motor function, activities of daily living, and quality of life in stroke patients with hemiplegia. These preliminary findings support the feasibility of this approach and highlight the need for large-scale studies to validate its effectiveness.